Biodegradable agar extracted from gracilaria vermiculophylla: films properties and application to edible coating - Sousa, A. M. M. (2010)
Gracilaria is a red algal genus that biosynthesizes a polymer called agar that is extensively used in the food and pharmaceutical industries as gelling and stabilizing agent. In the last years, many studies have focused on gel properties of this biopolymer; but the agar films and coatings still have few studies reported. The edible film and coating have a protective function, preventing moisture, oxygen and flavour transfers between food and surroundings. The objectives of this work are the production of biodegradable agar films from Gracilaria vermiculophylla, collected in Ria de Aveiro, Portugal, and the study of the effect of glycerol, an hydrophilic plasticizer, on the properties of the films and on subsequent application in edible coating of fresh fruits and vegetables. The agar extraction was carried out at specific optimum parameters determined in previous work (3.5 h pre-treatment duration, 6% NaOH concentration and 2 h extraction time). Agar films were made using the knife coating technique and compared with commercial agar. The physical properties of films such as hygroscopicity, mechanical resistance (Young’s modulus, tensile strength and elongation), and permeability to water vapour and oxygen were characterized. As expected, the plasticizer addition revealed and increase on elongation and decrease on tensile strength. The films were transparent and optically clear, showing good properties similar to the commercial agar films. The potential application of the agar/glycerol solution to fresh vegetable preservation was tested. Model fruits and vegetables were coated with the biopolymer/plasticizer solution and compared with a control sample in terms of colour, firmness, weight loss and shelf life. Considering on one hand the abundance of the raw algal material which is actually an invasive species, and the properties of the agar films and coatings obtained on the other hand, commercial use of G.vermiculophylla from Ria de Aveiro is well justified.